Pt doped (8,0) single wall carbon nanotube as hydrogen sensor: A density functional theory study - Fellah, Mehmet Ferdi (Pergamon-Elsevier Science Ltd, 2019)
In this study, it has been investigated the use of Pt doped carbon nanotube for the hydrogen gas sensor at room temperature and compared with available experimental literature data. The WB97XD method with 6-31G(d,p) and LanL2DZ basis sets have been utilized. The charge distributions obtained for the structures show that charge transfer is occurred from the adsorbed hydrogen molecule to the Pt atom of carbon nanotube structure as an electron acceptor. The HOMO-LUMO gap of the Pt doped SWCNT decreased with the adsorption of hydrogen molecule. As a conclusion, the electrical conductivity of Pt doped (8,0) SWCNT cluster increased after a hydrogen molecule adsorption. Accordingly, Pt doped (8,0) SWCNT has potential for sensing of hydrogen gas. Theoretical (DFT) results are in well agreement with available experimental literature data that was reported a chip sensor loaded Pt-CNT gave highest response coefficient for H-2 gas sensing. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
FELLAH, Mehmet Ferdi/0000-0001-6314-3365
Keywords: (8,0) SWCNT; Pt atom; Hydrogen; Sensor; Adsorption; DFT